Effects of High Salt-intake on Renal Injury and Fibrosis in C57BL/6J Mice - Yuying CHENG; Shudan TAN; Yanlan CHEN; Darong HUANG; Xinyu DENG; Junyuan HUANG; Haozhang HUANG; Pan LI; Bing DU (Shipin gongye ke-ji, 2023)
In order to further explore the effects of high salt intake on kidney of ordinary mice, C57BL/6J mice were randomly allocated into normal control group (NC), 4% high salt intake group (4% group) and 8% high salt intake group (8% group), which were fed with 0.5%NaCl normal diet, 4% or 8% high salt diet respectively. The renal function index, inflammatory factor secretion, pathological damage and fibrosis degree of mice from different groups were compared. The results indicated that high salt intake led to renal function injury in C57BL/6J mice. The contents of serum creatinine, serum urea nitrogen and urine Na were significantly increased, whereas the content of urine creatinine was significantly decreased. The 8% high salt diet showed further renal damage when compared to the 4% high salt diet, which include further decrease in urine creatinine and an increase in serum urea nitrogen. Compared with NC, 4% and 8% high salt intake also increased the secretion of inflammatory cytokines TNF-α、IL-6 and IL-1β in kidney, and the secretion of IL-6 and IL-1β was further increased in the 8% group compared with the 4% group. As the HE and Masson staining results shown, high salt intake caused renal fibrosis and pathological damage of cortex and medulla in C57BL/6J mice, and the 8% group was more severe than the 4% group. High salt diet induces kidney injury and fibrosis in C57BL/6J mice, and increasing salt intake can further aggravate the severity of injury and fibrosis.